2011
DOI: 10.1371/journal.pone.0024393
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Pro-Inflammatory Cytokine Responses following Toll-Like-Receptor Ligation in Schistosoma haematobium-Infected Schoolchildren from Rural Gabon

Abstract: Background Schistosoma infection is thought to lead to down-regulation of the host's immune response. This has been shown for adaptive immune responses, but the effect on innate immunity, that initiates and shapes the adaptive response, has not been extensively studied. In a first study to characterize these responses, we investigated the effect of Schistosoma haematobium infection on cytokine responses of Gabonese schoolchildren to a number of Toll-like receptor (TLR) ligands.MethodologyPeripheral blood monon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
2
13
2
Order By: Relevance
“…However, the before mentioned have focused on the adaptive responses and include Tregs [6][9]. It should be noted that, in line with the current data, a recent study in Gabon found that S. haematobium infected children develop a more pro-inflammatory TLR-mediated response [30]. We did not observe substantial differences in STH species and their effects on CVD risk factors.…”
Section: Discussionsupporting
confidence: 86%
“…However, the before mentioned have focused on the adaptive responses and include Tregs [6][9]. It should be noted that, in line with the current data, a recent study in Gabon found that S. haematobium infected children develop a more pro-inflammatory TLR-mediated response [30]. We did not observe substantial differences in STH species and their effects on CVD risk factors.…”
Section: Discussionsupporting
confidence: 86%
“…This is in contrast to studies where helminth infections were found to influence TLR responses or expression levels [18], [34], [38], [39]. This may be due to the difference between whole blood responses measured here and isolated peripheral blood mononuclear cells used in the other studies.…”
Section: Discussioncontrasting
confidence: 85%
“…In contrast, T cells obtained from mice given DCs cotreated with SEA and Propionibacterium acnes antigen had a robust SEA-specific induction of IL-17 (34), supporting the view that helminth plus bacterial infections can drive significant pro-inflammatory events that are absent in helminth-only infected individuals. In accordance with this, peripheral blood mononuclear cells from Gabonese children infected with Schistosoma haematobium have enhanced TNFa output in response to Toll-like receptor (TLR)-2 agonists compared to cells from uninfected children [a similar trend was noted for challenge with the TLR4 agonist lipopolysaccharide (LPS)] (35). It has also been reported that DCs from individuals infected with N. americanus have increased expression of CD14, the LPS coreceptor and this would allow for the possibility of increased responsiveness to endotoxin (36).…”
Section: Helminths and Bacterial Pathogensmentioning
confidence: 67%